Evaluating the Impact of Managed Care on Service Use and Disparities in Care Among Children and Adolescents Receiving Medicaid - Eberly, Todd (The Hilltop Institute, 2007)
This policy brief, based on research conducted by Dr. Todd Eberly for his dissertation, examines whether a transition from fee-for-service to a managed care Medicaid program improved access to preventive well care services, and whether there were differential effects on service use for racial and ethnic minority youth.
Keywords: managed care; Medicaid; enhancing the receipt; role of managed care in enhancing access to care